2021
DOI: 10.1186/s13148-021-01054-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in cord blood in association with prenatal depressive symptoms

Abstract: Background Prenatal symptoms of depression (PND) and anxiety affect up to every third pregnancy. Children of mothers with mental health problems are at higher risk of developmental problems, possibly through epigenetic mechanisms together with other factors such as genetic and environmental. We investigated DNA methylation in cord blood in relation to PND, taking into consideration a history of depression, co-morbidity with anxiety and selective serotonin reuptake inhibitors (SSRI) use, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…In a different cohort, Kallak et al reported 13 CpGs differentially methylated by SSRI exposure status in cord blood 69 . Though cord blood DNAme is very distinct from placenta, we sought to evaluate whether any of the 14 CpGs reported by Cardenas et al 68 or Kallak et al 69 were also differentially methylated by SSRI exposure status in the placenta. At the CpG reported by Cardenas et al (cg22159528) we found no difference in DNAme by SSRI exposure (nominal p value > 0.05), see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different cohort, Kallak et al reported 13 CpGs differentially methylated by SSRI exposure status in cord blood 69 . Though cord blood DNAme is very distinct from placenta, we sought to evaluate whether any of the 14 CpGs reported by Cardenas et al 68 or Kallak et al 69 were also differentially methylated by SSRI exposure status in the placenta. At the CpG reported by Cardenas et al (cg22159528) we found no difference in DNAme by SSRI exposure (nominal p value > 0.05), see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At one of the 13 CpGs reported by Kallak et al, we found nominally significant ( p < 0.05) differential DNAme associated with SSRI exposure status in the placenta in the same direction as the original cord blood association: higher DNAme in SSRI-exposed cases. This was cg00331486 in LOC284930 on chromosome 22, which encodes a MYC-interacting long noncoding RNA species 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies employing EPIC array on neonatal tissues in association with maternal stress and/or anxiety are limited to one study by Kallak et al [ 75 ]. These authors investigated DNA methylation in cord blood of newborns exposed to maternal depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main neurobiological mechanisms of depression is dysregulated and dysfunctional stress response system (such as hypothalamic-pituitary-adrenal (HPA) axis activity and glucocorticoid receptor (GR) sensitivity) to show the adaptive change ( Guo et al, 2021 ). Moreover, prenatal depressive symptoms might influence fetal epigenetic programming ( Kallak et al, 2021 ). Prenatal depression is associated with differential methylation in GNAS, CTNNA2, OSBPL10, and 5-HTTLPR ( Sales et al, 2021 , Drzymalla et al, 2021 ).…”
Section: Epigenetics and Dna Methylationmentioning
confidence: 99%